Multiple downy mildew effectors target the stress‐related NAC transcription factor LsNAC069 in lettuce. (4th July 2019) - Meisrimler, Claudia‐Nicole; Pelgrom, Alexandra J. E.; Oud, Bart; Out, Suzan; Van den Ackerveken, Guido
Summary: To cause disease in lettuce, the biotrophic oomycete Bremia lactucae secretes potential RxLR effector proteins. Here we report the discovery of an effector‐target hub consisting of four B. lactucae effectors and one lettuce protein target by a yeast‐two‐hybrid (Y2H) screening. Interaction of the lettuce tail‐anchored NAC transcription factor, LsNAC069, with B. lactucae effectors does not require the N‐terminal NAC domain but depends on the C‐terminal region including the transmembrane domain. Furthermore, in Y2H experiments, B. lactucae effectors interact with Arabidopsis and potato tail‐anchored NACs, suggesting that they are conserved effector targets. Transient expression of RxLR effector proteins BLR05 and BLR09 and their target LsNAC069 in planta revealed a predominant localization to the endoplasmic reticulum. Phytophthora capsici culture filtrate and polyethylene glycol treatment induced relocalization to the nucleus of a stabilized LsNAC069 protein, lacking the NAC‐domain (LsNAC069 Δ NAC ). Relocalization was significantly reduced in the presence of the Ser/Cys‐protease inhibitor TPCK indicating proteolytic cleavage of LsNAC069 allows for relocalization. Co‐expression of effectors with LsNAC069 Δ NAC reduced its nuclear accumulation. Surprisingly, LsNAC069 silenced lettuce lines had decreased LsNAC069 transcript levels but did not show significantly altered susceptibility to B. lactucae . In contrast, LsNAC069 silencing increased resistance to Pseudomonas cichorii bacteria and reduced wilting effects under moderate drought stress, indicating a broad role of LsNAC069 in abiotic and biotic stress responses. Significance Statement: To infect lettuce, the obligate biotrophic oomycete Bremia lactucae secretes a large arsenal of RXLR‐effector proteins. We show that four RXLR‐like effectors target the endoplasmic reticulum‐associated host LsNAC069 transcription factor at its membrane‐associated C‐terminal region and hinder immune stress‐induced relocalization to the nucleus. We reveal membrane‐associated NACs as conserved effector targets to reduce immune activation. Furthermore, LsNAC069 is not only involved in plant immunity but also in drought stress adaptation.